Sex differences in systemic bone and muscle loss following femur fracture in mice. Issue 4 (13th June 2021) - Osipov, Benjamin; Paralkar, Manali P.; Emami, Armaun J.; Cunningham, Hailey C.; Tjandra, Priscilla M.; Pathak, Suraj; Langer, Henning T.; Baar, Keith; Christiansen, Blaine A.
Abstract: Fracture induces systemic bone loss in mice and humans, and a first (index) fracture increases the risk of future fracture at any skeletal site more in men than women. The etiology of this sex difference is unknown, but fracture may induces a greater systemic bone loss response in men. Also sex differences in systemic muscle loss after fracture have not been examined. We investigated sex differences in systemic bone and muscle loss after transverse femur fracture in 3‐month‐old male and female C57BL/6 J mice. Whole‐body and regional bone mineral content and density (BMC and BMD), trabecular and cortical bone microstructure, muscle contractile force, muscle mass, and muscle fiber size were quantified at multiple time points postfracture. Serum concentrations of inflammatory cytokines (IL‐1β, IL‐6, and TNF‐α) were measured 1‐day postfracture. One day postfracture, IL‐6 and Il‐1B were elevated in fracture mice of both sexes, but TNF‐α was only elevated in male fracture mice. Fracture reduced BMC, BMD, and trabecular bone microstructural properties in both sexes 2 weeks postfracture, but declines were greater in males. Muscle contractile force, mass, and fiber size decreased primarily in the fractured limb at 2 weeks postfracture and females showed a trend toward greater muscle loss. Bone and muscle properties recovered by 6 weeks postfracture. Overall, postfracture systemic bone loss is greater in men, which may contribute to sex differences in subsequent fracture risk. In both sexes, muscle loss is primarily confined to the injured limb and fracture may induce greater inflammation in males.